ANALISIS PERHITUNGAN DAN PENCATATAN PPH PASAL 23 DAN PELAPORAN PPH PASAL 25 PADA PT. BANK SULUT CABANG UTAMA - Lumunon, Cisilia; Saerang, David Paul Elia; Elim, Inggriani (Universitas Sam Ratulangi, 2014)
Income tax article 23 ( article 23 ) , is withholding tax on income derived by a taxpayer in domestically and Permanent Establishment derived from the capital , organizing the delivery of services or activities other than those of Article 21 Income Tax withheld , paid , supplied , to be paid , or was due for payment by government agencies , subject to tax in domestically , organizers of the event , the permanent establishment , representatives of other foreign companies . While the Income Tax Article 25 is that income tax installment must be paid by the taxpayer for any month in the current tax year. This study aims to determine the amount of income tax Article 23 and Income Tax Article 25 are deposited and to know whether the calculation and recording of income tax under Article 23 and Article 25 of the Income Tax Reporting at PT. Bank Sulut Main Branch is in conformity with the Law on Income Tax. The object of research is taken at PT. Bank Sulut Main Branch. The method used is descriptive analysis method. From the results of this study concluded that the calculation and recording of article 23 and article 25 of Income Tax Reporting was in accordance with applicable regulations.